1998
DOI: 10.1111/j.1440-1681.1998.t01-17-.x
|View full text |Cite
|
Sign up to set email alerts
|

COSEGREGATION OF THE Tnfα LOCUS WITH CARDIOVASCULAR PHENOTYPES IN THE F2 GENERATION OF A NEW ZEALAND GENETICALLY HYPERTENSIVE AND BROWN NORWAY CROSS

Abstract: 1. The association of the Tnfalpha locus with several cardiovascular phenotypes and body mass has been studied in the F2 generation of a reciprocal cross between rats of the New Zealand genetically hypertensive (GH) and the normotensive Brown Norway (BN) strains. In the total F2 population the GH allele of Tnfalpha cosegregated with increased intra-arterial blood pressure (BP) in a recessive manner. A similar but weaker effect was observed for tail BP. 2. An association between genotype and body mass in female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…29 A BP QTL within the same region of rat chromosome 20 was also identified in a cross involving New Zealand genetically hypertensive and BN rats. 45 No significant effect of the differential segment was found in some other studies, however. 28,46 …”
Section: Discussionmentioning
confidence: 64%
“…29 A BP QTL within the same region of rat chromosome 20 was also identified in a cross involving New Zealand genetically hypertensive and BN rats. 45 No significant effect of the differential segment was found in some other studies, however. 28,46 …”
Section: Discussionmentioning
confidence: 64%
“…While associations between some cardiovascular phenotypes and several candidate gene alleles (GCA, REN, TNF α) in GH rats have already been reported in a GH × BN intercross (19,40,41), we report, for the first time, all data and results of the complete genome scan including QTL for five of the six measured or derived traits on six different chromosomes. Three major blood pressure QTL in the GH rat were identified (1 significant QTL on chromosome 6 and 2 suggestive on chromosomes 2 and 18).…”
Section: Discussionmentioning
confidence: 99%
“…20 In addition, the body temperature response to lipopolysaccharide differs between SHR and its normotensive control, 33 and it has been demonstrated that this response is, at least in part, determined by the TNF-␣ gene locus. 34 Finally, the TNF-␣ gene locus as a part of the RT1 complex has been suggested in some, 35,36 but not all, 37,38 studies to contribute to the pathogenesis of hypertension in SHR and New Zealand genetically hypertensive rats. In the present study, the effect of the TNF-␣ gene locus on both obesity and obesity-associated hypertension was found to be most significant in nonmorbidly obese individuals.…”
Section: Discussionmentioning
confidence: 99%